Determinants of Shariah Banking Performances in Indonesia Through the Perspective of Economic and Social Level - Malini, Helma (Fakultas Ekonomi dan Bisnis, UNTAN, 2020)
Shariah bank has become the core of Indonesia financial industry. In the implementation, Shariah banking in Indonesia is integrated with social issues since the basic fundamental of Shariah banking industry are from religions and regulations. In detail the return are not solely depends on society demand but also related with moral issues. As corruption that kept on happening and political instability makes Shariah Banking industry in Indonesia sensitive and fragile towards socio economic development happening during certain period. This paper attempt to investigate the socio economic factors together with bank specific factors of Indonesia Shariah Banks by using GMM and Quantile regression. The dataset used or in this study involves 34 Shariah banks in Indonesia. In this study, Return on Assets has been found significantly positive to bank specific factors such as credit risk and statistically negative to cost to income ratio. However, it has been found that the relationship between risk and return is heterogenous or dissimilar accross different quantiles. Findings of the study tend to reveal that the socio economic factors particularly corruption, political stability and investment freedom have positive and significant relation to the Shariah bank performances in Indonesia.